Remote Online Competition System in Rhythmic Gymnastics - Hakala, Sofia (My University, 2023)
The start of the global COVID-19 pandemic was a big hit for all sports communities around the world in March 2020. As the virus spread around the globe, sports halls began closing, all competitions, tournaments and even regular trainings had to be cancelled. The gymnastics community quickly assessed the situation and virtual training sessions became the new norm around the world. The virtual world was then utilised to arrange online competitions for gymnasts to compete in. The online competitions were either held with pre-filmed videos sent to the competition or with live online performances through an application like Zoom. This master’s thesis presents the results from a study on how usable a Finnish system for online competitions was according to the systems users, as well as a redesigned version of the system based on user input. The original system is based on a web application with a scoring system on one web page, a live stream on another and a Zoom application open on the same or a on another device. The redesigned system utilises only a scoring system and Zoom, removing the live stream completely. The results show that most of the users were overall happy with the original system and especially liked the scoring system of the application. The study also showed that more than half of the participants wished for it to be possible to use the system with only one device or monitor, or at least for the scoring and live stream to work on the same page. The redesigned system removed the need for a live stream by using preloaded videos, which was seen as a positive change by the users.
Keywords: remote competition, rhythmic gymnastics